Phytochemical screening and properties of botanical crude extracts and ethyl acetate fractions isolated by deep eutectic solvent - Saied Aboushanab; Vadim Shevyrin; Mustapha Kamel; Jonas Kambele; Elena Kovaleva (Chimica Techno Acta)
Botanicals, being safe because of their natural origin, are associated with potential health benefits due to their isoflavones-rich content. Isoflavones as plant-generated secondary metabolites are formed to defend against environmental stress such as UV radiation, mechanical damage, or any other attack from the surroundings. Kudzu (Pueraria roots and flowers), red clover (Trifolium pratense), and soy (Glycine max) are of significant importance in the medical field. Isoflavones were reported to exhibit a variety of biological functions, e.g., antiaging, anticancer, and microbiome modulations. This study focuses attention on the extraction and quantification of isoflavones from kudzu roots (KR), kudzu flowers (KF), red clover (RC), and soy molasses (SM), and determining their total polyphenols (TPC), flavonoids (TFC), and antioxidant activity (AOA). Novel green ultrasound-assisted extraction (UAE) technology was developed to extract and quantify the isoflavones. The results showed the quantity of isoflavones in KR, KF, RC, and SM crude extracts to be 1.01%, 2.9%, 0.70% and 0.67%, respectively. The fractionation using ethyl acetate (EA) improved the yield that became 1.48%, 2.5%, 1.3% and 0.89% in the KR, RC and SM extract fractions, respectively. This investigation eventually showed that our green UAE methodology is a safe and efficient method for recovering isoflavones. The total isoflavone contents were recorded as follows: KFKRRCSM. We concluded that these botanicals are a crucial source of isoflavones that exhibit strong antioxidant properties.